A STUDY OF COUPLE-STRESS FLUID FLOW IN AN ELASTIC TUBE (International Journal of Food and Nutritional Sciences, 2022)
Abstract: The expressions for velocity and flux flow rate are determined by using Homotopic Perturbation method, in the process of long wave length and low Reynold’s number approximations. The variation of flux is calculated by Rubinow and Keller, Muzumdar methods. The effects of different criterias on velocity and flux have been discussed.